Poblamiento, recursos y circulación de mercancías en el Garb al-Andalus: la contribución de la cerámica - Gómez Martínez, Susana (2021)
Historiography usually considers the Garb as a marginal area in relation to the rest of al-Andalus due to the reduced ntervention of the central powers, especially the Umayyad emirs. This marginality has been attributed to both socio-political reasons (the volatility of the loyalties of local aristocracies) and economic ones (poverty of natural resources and fragility of exchange networks). We have some general assessment on the resources of the territory, but they are not sufficiently detailed about their regional characterization. The lack of sources, both written and material, make ceramics one of the most helpful way for the analysis of the relations between settlement, resources and the circulation of goods in Garb al-Andalus for this period between the 8th and 13th century.